1981
DOI: 10.1080/00913847.1981.11711187
|View full text |Cite
|
Sign up to set email alerts
|

Intercollegiate Lacrosse Injuries

Abstract: In brief:Injury data for an intercollegiate lacrosse team were collected after one season of practices and games and compared with injury data from a summer league team. Only five players (15%) completed the season without injury, and there were 78 total injuries to the 34 players. The most frequent injury was ankle sprain. The experience, skills, and age of collegiate athletes are more homogeneous and they often have superior equipment and playing surfaces, which suggests that they should have fewer injuries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Ekstrand and Gillqvist (1982) have found 8/1000 in adult players. In other contact sports such as lacrosse, the risk of injury is as high as 13/1000 training hours and 443/1000 game hours (Nelson et al, 1981). Accurate injury data from winter sports are difficult to obtain but rough estimates show 10/1000 skier-days in downhill skiing (Ellison, 1972) and 0.5/1000 skierdays in cross country skiing (Garaick, 1971).…”
Section: Resultsmentioning
confidence: 99%
“…Ekstrand and Gillqvist (1982) have found 8/1000 in adult players. In other contact sports such as lacrosse, the risk of injury is as high as 13/1000 training hours and 443/1000 game hours (Nelson et al, 1981). Accurate injury data from winter sports are difficult to obtain but rough estimates show 10/1000 skier-days in downhill skiing (Ellison, 1972) and 0.5/1000 skierdays in cross country skiing (Garaick, 1971).…”
Section: Resultsmentioning
confidence: 99%
“…The forefoot can become fixed on the turf, and externally applied forces to the foot can result in this injury. Interestingly, studies (Ekstrand et al (21), Nelson et al (22), and Nielsen et al (23))have not shown an increase in turf toe injuries in either soccer or lacrosse players using artifical turf, in contrast to American football players using the same type playing fields. The lack of significant body contact, and resulting high externally applied force/moments may account for this difference.…”
Section: Playing Surfacesmentioning
confidence: 91%